2011
DOI: 10.1080/08870446.2011.562606
|View full text |Cite
|
Sign up to set email alerts
|

Emotional competence and quality of life of children with asthma: The mediating effect of coping strategies

Abstract: This study explored the mediating effect of coping strategies on the relationship between emotional competence (EC) and quality of life (QOL) among children with asthma. Participants were 87 children (M age = 11.72, SD = 2.58) with controlled and partially controlled asthma, undergoing everyday treatment. They filled in questionnaires assessing EC, coping strategies and QOL. Results showed that the association between some ECs and the QOL of children with asthma was fully mediated by two maladaptive cognitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
13
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 39 publications
4
13
0
2
Order By: Relevance
“…The importance of the first three components is corroborated by previous studies (Lahaye, Fantini-Hauwel, Van Broeck, Bodart, & Luminet, 2011;van der Veek, Nobel, et al, 2012). However, the prediction power of Verbal sharing was rather new, although some authors found similar relations between low experience of somatic complaints and good communication with parents, in children aged 11-13 years old (Ottova et al, 2012); low verbal expression of emotions in adolescents with bulimia nervosa (Sim & Zeman, 2010), or in asthmatic children with low quality of life (Lahaye, Van Broeck, Bodart, & Luminet, 2013).…”
Section: Discussionsupporting
confidence: 71%
“…The importance of the first three components is corroborated by previous studies (Lahaye, Fantini-Hauwel, Van Broeck, Bodart, & Luminet, 2011;van der Veek, Nobel, et al, 2012). However, the prediction power of Verbal sharing was rather new, although some authors found similar relations between low experience of somatic complaints and good communication with parents, in children aged 11-13 years old (Ottova et al, 2012); low verbal expression of emotions in adolescents with bulimia nervosa (Sim & Zeman, 2010), or in asthmatic children with low quality of life (Lahaye, Van Broeck, Bodart, & Luminet, 2013).…”
Section: Discussionsupporting
confidence: 71%
“…In order to help the adolescents self-regulate their emotional response, it may be important to explore the frequency or duration of symptom episodes when tiredness is reported as a “feeling.” Emotional responses have an important implication for adolescents’ coping with uncontrolled asthma. Studies have shown that negative emotions could trigger or prolong asthma symptoms (Bender & Zhang, 2008; Richardson et al, 2006; Tibosch, Verhaak, & Merkus, 2011), elicit counterproductive coping mechanisms (e.g., overcompensation or denial),(Barton, Clarke, Sulaiman, & Abramson, 2003; Lahaye, Fantini-Hauwel, Van Broeck, Bodart, & Luminet, 2011) or undermine adherence to treatment (Barton et al, 2003; Drotar & Bonner, 2009). On the other hand, some participants showed a tendency to downplay or normalize asthma symptoms by expressing neutral to positive feelings.…”
Section: Discussionmentioning
confidence: 99%
“…La importancia de estos componentes se ve apoyada por estudios previos (Lahaye et al, 2011b;van der Veek et al, 2012b). En el caso de las tres primeras escalas, la relación era negativa, presentando los menores con más quejas somáticas, problemas para diferenciar entre emociones, analizar las suyas propias y comunicarlas, es decir, su conciencia emocional, más que específica, era global.…”
Section: Discussionunclassified
“…Dado que la reflexión consciente sobre la experiencia emocional permite al niño interrumpir el programa emocional en marcha y ganar en flexibilidad, adaptándose a la nueva situación, la baja conciencia emocional puede verse reflejada en niños con conducta agresiva, con síntomas depresivos, etc. (Stegge y Meerum Terwogt, 2007), o bien disminuir la utilización de estrategias adaptativas de regulación cognitiva, por ejemplo, en casos de enfermedad crónica (Lahaye, Fantini-Hauwel, Van Broeck, Bodart y Luminet, 2011b).…”
Section: Introductionunclassified